Polyploidy - Curtis, Katherine; Hallaq, Tom (Kansas State University, 2017)
A team of three scientists from Kansas State University, Michigan State University and the Desert Botanical Garden are investigating polyploidy (the condition of having more than one set of chromosomes) and diversity in the plant genus Phlox (Polemoniaceae). While polyploidy is considered to play an important role in plant evolution, our current knowledge of ploidy level variation relative to diversity is limited. This project investigates questions of general interest on polyploidy and diversity and integrates findings to advance a broader understanding of the role of polyploidy in the diversification of plants.
Keywords: Ferguson, Carolyn J.